2014
DOI: 10.1155/2014/316463
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion Practice before and after Implementation of Type and Screen Protocol in Emergency Department of a University Affiliated Hospital in Iran

Abstract: Background. Blood transfusion is the cornerstone of therapy for many serious and common diseases. This study was performed to assess blood transfusion practice before and after implementation of type and screen protocol in emergency department of a university affiliated hospital in Iran, 2012-2013. Methods. An audit was studied before and after the implementation of type and screen protocol. The number of blood transfusions, time interval between blood order and transfusion, cross-match to transfusion ratio (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
3
16
0
Order By: Relevance
“…This leads to increased waste, larger inventories, and increased departmental costs. 4,9,12,13 Other variables must be considered to effectively assess the need for crossmatching units to a patient and include: preoperative hemoglobin level, predicted blood loss, patient blood volume and likelihood of transfusion 5,6,9,12,13 These variables should all be used in conjunction to evaluate patient needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to increased waste, larger inventories, and increased departmental costs. 4,9,12,13 Other variables must be considered to effectively assess the need for crossmatching units to a patient and include: preoperative hemoglobin level, predicted blood loss, patient blood volume and likelihood of transfusion 5,6,9,12,13 These variables should all be used in conjunction to evaluate patient needs.…”
Section: Discussionmentioning
confidence: 99%
“…This is a widely accepted method to monitor product use, a 2.0 benchmark is generally considered appropriate. 8,13,14 Apparent in a United Kingdom study, Mundy et al 9 concluded that 77% of total hip and 62% of total knee surgeries requested units which were never used.…”
Section: Introductionmentioning
confidence: 99%
“…The screening and identification of red blood cell (RBC) alloantibodies is performed as pre-transfusion testing (Type and Screen) and in pregnancy to detect potential hemolytic disease of the fetus and newborn (HDFN). A low ionic strength solution (LISS) indirect antiglobulin test (IAT) is considered the most suitable for the detection of clinically significant antibodies because of its speed, sensitivity and specificity [1,2]. According to several international guidelines (such as BSH (British Society for Haematology) and CBO ('Centraal Begeleidingsorgaan') [3], the screening cell set must answer to certain requirements such as the inclusion of at least one cell with homozygous expression of the Fy a , Fy b (Duffy antigens), Jk a , Jk b (Kidd antigens), S and s antigens (MNSs antigens) and heterozygous expression for the K (Kell) antigen [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The Type and Screen (T&S) is a reliable alternative for the management of these situations [1,2]. The T&S includes typing the patient's RBCs for ABO and Rh blood groups, and screening patient's serum for the presence of alloantibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, procedures for blood product release according to the T&S and electronic XM have been adopted in several European countries, and their implementation has been advocated by the Italian transfusion regulation as well [5]. Actually, the adoption of T&S procedure and electronic XM in selected patient populations support the rational allocation of blood resources [1,2,4]. …”
Section: Introductionmentioning
confidence: 99%